Association of low skeletal muscle mass and systemic inflammation with surgical complications and survival after microvascular flap reconstruction in patients with head and neck cancer. Issue 10 (2nd June 2022) - Chargi, Najiba; Breik, Omar; Forouzanfar, Tymour; Martin, Timothy; Praveen, Prav; Idle, Matthew; Parmar, Satyesh; de Bree, Remco
Abstract: Background: Skeletal muscle mass (SMM) and chronic inflammation are associated with postoperative complications and survival. Methods: Patients with head and neck cancer (HNC) undergoing microvascular free flap reconstruction were included. SMM and neutrophil‐to‐lymphocyte ratio (NLR) were measured and their association with treatment outcomes analyzed. Results: Five hundred and fifty‐four patients were included. Predictors for complications were elevated NLR in all flaps (OR 1.5), low SMM in radial forearm flap (OR 2.0), and elevated NLR combined with low SMM in fibula flap surgery (OR 4.3). Patients with solely elevated NLR were at risk for flap‐related complications (OR 3.0), severe complications (OR 2.2), and when combined with low SMM for increased length of hospital stays (LOS) (+3.9 days). In early‐stage HNC, low SMM (HR 2.3), and combined elevated NLR with low SMM (HR 2.6) were prognostics for decreased overall survival. Conclusions: SMM and NLR are predictive for poor outcomes in patients with HNC undergoing microvascular reconstruction.